STEM and CRT Learning: A Sasambo-Based Comparative Analysis of Students’ Critical Thinking and Creativity - Saskia Syalsa Zabillah JR; Nanang Rahman; Syafruddin Muhdar (MIMBAR PGSD Undiksha, 2025)
Proficiency in critical and creative thinking are fundamental skills that students must have to face the challenges of the 21st century. This study compared the effectiveness of STEM (science, technology, engineering and mathematics) education and CRT based on Sasambo education in improving students' critical and creative thinking skills in elementary schools. This study used a quantitative approach with a quasi-experimental design and a pre-test-post-test control group. A total of 31 students participated in this study and were divided into two experimental groups. The first experiment used the STEM approach, while the second experiment used CRT based on Sasambo culture. Data was collected through an essay test that evaluated students' critical thinking (10 questions) and creative thinking (4 questions). In addition, descriptive statistics, homogeneity, normality, paired sample t-test, and N-Gain scores were used to evaluate students' improvement. This study shows that different learning approaches can have diverse impacts on students' cognitive skill development. STEM education proved to be more effective in improving critical thinking, while culture-based CRT was superior in encouraging students' creativity. The findings showed that STEM-based education significantly improved students' critical thinking skills more than CRT-based education. Conversely, CRT was more effective in improving students' creative thinking skills. This highlights the importance of integrating educational innovations with local customs to support the growth of students' critical thinking and creativity.